Factors associated with reduced substance use and treatment completion among justice-involved pregnant women - Moore, John; Murphy, Melissa G.; Spitz, Austin; Goldfarb, Samantha (Frontiers in Psychiatry, 2026)
IntroductionPregnant women with criminal justice-system involvement (CJI) and substance use disorders (SUD) face considerable barriers that impact substance use treatment outcomes. However, limited research has investigated such factors among this population. To address this gap, we investigated associations of sociodemographic and treatment-related factors with reduced substance use and treatment completion among CJI pregnant women who utilized outpatient treatment.MethodsData came from the 2021–2022 Treatment Episode Dataset-Discharges (TEDS-D). The sample included 1,903 CJI pregnant women discharged from outpatient treatment. Multivariable logistic regression was used to measure associations of sociodemographic and treatment-related predictors with reduced substance use and treatment completion.ResultsCompared to alcohol use, marijuana use was associated with lower odds of reduced use, whereas opioid and stimulant use were each associated with lower odds of treatment completion. Self-help group attendance was associated with higher odds of both outcomes.DiscussionFindings suggest that substance type may be an important consideration for treatment planning. Examining substance-specific factors that facilitate positive treatment outcomes is a practical next step for future studies. Self-help groups were a key facilitator of positive outcomes, suggesting that the integration of peer recovery support models into formal substance use treatment services warrants consideration.